(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ever since the dawn of civilization, there has been a struggle to emancipate women from male oppression. In the past, the work by the women authors has always been undervalued because of some patriarchal assumptions. Feminism is an expression of resentment at the unjust treatment meted out to any woman. In literature, it refers to any mode that approaches a text with foremost concern for the nature of female experience. The inequalities against which the feminist have raised their voice of protest-legal, economics and social restriction on the basic rights of woman can be traced throughout history. The term ’feminism’ has its origin from the Latin word lemina’ meaning ’woman’ (through French leminisme’). It refers to the advocacy of women’s rights, status and power at par with men on the grounds of ’equality of sexes’. In other words, it relates to the belief that women should have the same social, economic and political rights as men. The study aims to find out if Shashi Deshpande’s women really assert themselves or somewhere in their assertion process conform to endurance. For the purpose of this study, all her novels have been considered, but the thrust of this research is on three of her major novels viz., The Dark Holds No Terrors, Roots and Shadows and That Long Silence. These three novels have won awards and have been translated into a number of foreign languages.